European Property Law Journal (De Gruyter, 2011)
The EPLJ focuses on private and public law aspects of land, movables, claims and new objects of property law, such as virtual property. Articles are based upon comparative legal analysis and examine property law from a European perspective. This includes not only the multidisciplinary study of property law and the effects of the EU internal market on the national property law systems, but also the philosophical and ideological aspects.